Evolution of influenza A virus in intensive and free-range swine farms in Spain. Issue 2 (30th November 2021) - Encinas, Paloma; del Real, Gustavo; Dutta, Jayeeta; Khan, Zenab; van Bakel, Harm; del Burgo, M Ángeles Martín; García-Sastre, Adolfo; Nelson, Martha I
Abstract: Swine harbor genetically diverse influenza A viruses (IAVs) with the capacity to host-switch to humans, causing global pandemics. Spain is the largest swine producer in Europe and has a mixed production system that includes 'white coat' pigs raised intensively in modern buildings and free-range Iberian pigs that interface differently with humans, wildlife, and other swine. Through active longitudinal IAV surveillance in nine Spanish provinces during 2015–9, we generated forty-seven complete or near-complete genome sequences from IAVs collected from swine in both systems. Genetically diverse IAVs were identified in intensively raised white pigs and free-range Iberian pigs, including new H3N1 reassortants. Both systems are dynamic environments for IAV evolution, but driven by different processes. IAVs in white pigs were genetically related to viruses found in swine raised intensively in other European countries, reflecting high rates of viral introduction following European trade routes. In contrast, IAVs in Iberian pigs have a genetic makeup shaped by frequent introductions of human IAVs, reflecting rearing practices with high rates of human contact. Transmission between white and Iberian pigs also occurred. In conclusion, Iberian swine with high rates of human contact harbor genetically diverse IAVs and potentially serve as intermediary hosts between white pigs and humans, presenting an understudied zoonotic risk that requires further investigation.